Reconstruction for Complex Oromandibular Facial Defects: The Fibula Free Flap and Pectoralis Major Flap Combination - Mohammed Qaisi; Ryan Dee; Issam Eid; James Murphy; Ignacio A. Velasco Martinez; Henry Fung (Case Reports in Surgery)
Background. Extensive through-and-through oromandibular defects after advanced oral carcinoma excision pose a reconstructive challenge for the head and neck surgeon. These complex oromandibular wounds often involve the mandible, oral and/or aerodigestive mucosa, and the external skin. As a result, these defects are often not amenable to reconstruction with a single flap due to the volume of soft tissue needed and the three-dimensional reconstructive requirement. The use of two free flaps has often been suggested to overcome this reconstructive challenge. A simpler and less technically demanding way to deal with this may involve the use of a free flap in combination with a pedicled regional flap. We present our experience of the use of a simultaneous microvascular fibula free flap (FFF) with a pectoralis major myocutaneous flap (PMMC) for addressing these defects. Methods. A retrospective chart review was performed of patients treated with a FFF and PMMC combination for the reconstruction of oromandibular defects at the University of Mississippi Medical Center (Jackson, MS) between October 2013 and February 2016. A minimum follow-up of 12 months was required. Data collected included the extent and location of tumor involvement, size of the postablative defect, tumor histology, clinical and pathological staging, length of follow-up, functional outcomes, and associated complications. Results. A total of three patients were identified to have been treated with the above technique. Defects repaired involved through-and-through mandibular defects with associated oral mucosa and external skin defects. In all cases, the FFF was used for restoring bony continuity with the skin paddle used to reconstruct the intraoral lining. The PMMC was used for reconstruction of the external skin defect and for providing soft tissue bulk. The average size of the fibula skin paddle used for intraoral reconstruction was 7.7 cm×11.7 cm. The average size of the PMMC paddle was 7.3×9 cm. The mean follow-up was 21.7 months. Both the FFF and PMMC survived in all cases, although postoperative wound healing complications occurred in two of the three patients. There was one partial flap loss. Two patients regained good oral intake while one patient tolerated oral intake but was PEG tube-dependent. Conclusions. The combination of pectoralis major myocutaneous flap and a vascularized free fibular flap is a viable option for the reconstruction of complex through-and-through oromandibular defects. This technique may be useful when a single microvascular free flap is not sufficient for reconstruction of such defects.